Comparison of the Effectiveness of Theater-Based Art Therapy and Psychosocial Rehabilitation on Illness Perception and Autonomous Arousal Readiness in Patients with Schizophrenia - Abolghasemzade, Mona; Khajevandkhoshli, Afsaneh; Aziziziabari, Lilasadat (Mental Health and Lifestyle Journal, 2025)
The objective of this study was to compare the effectiveness of theater-based art therapy and psychosocial rehabilitation on illness perception and autonomous arousal readiness in male patients with schizophrenia. This applied study employed a semi-experimental pretest–posttest design with a control group and a three-month follow-up. The statistical population consisted of male patients aged 25–55 years with mild schizophrenia under the supervision of Iranmehr Comprehensive Care Center in Qaem Shahr, Iran, in 2024. Using G*Power software, a total sample of 45 participants was selected through purposive sampling based on inclusion and exclusion criteria, and they were randomly assigned to two experimental groups (theater-based art therapy and psychosocial rehabilitation, 15 each) and one control group (15 participants). The Illness Perception Questionnaire (Broadbent et al., 2006) and the Autonomous Arousal Readiness Questionnaire (Korn, 1998) were administered at three stages: pretest, posttest, and follow-up. Data were analyzed using repeated measures ANOVA, Bonferroni, and Tukey post hoc tests in SPSS version 18. The results of mixed repeated measures ANOVA indicated significant main effects of group, treatment stage, and group × stage interaction for both illness perception and autonomous arousal readiness (p < .001). Bonferroni post hoc tests showed that illness perception increased significantly from pretest to posttest and follow-up, while autonomous arousal readiness decreased significantly over the same periods, with no significant differences between posttest and follow-up, suggesting sustained effects. Tukey post hoc comparisons further revealed that psychosocial rehabilitation produced significantly greater improvements than theater-based art therapy in both illness perception (p < .001) and reduction of arousal readiness (p = .03). The findings demonstrate that both theater-based art therapy and psychosocial rehabilitation are effective interventions for enhancing illness perception and reducing autonomous arousal readiness in patients with schizophrenia, with psychosocial rehabilitation showing comparatively stronger effects.